Regulatory Pathways of Monoamine Oxidase A during Social Stress - Higuchi, Yuki; Soga, Tomoko; Parhar, Ishwar S. (Frontiers in Neuroscience, 2017)
Social stress has a high impact on many biological systems in the brain, including serotonergic (5-HT) system—a major drug target in the current treatment for depression. Hyperactivity of hypothalamic-pituitary-adrenal (HPA) axis and monoamine oxidase A (MAO-A) are well-known stress responses, which are involved in the central 5-HT system. Although many MAO-A inhibitors have been developed and used in the therapeutics of depression, effective management of depression by modulating the activity of MAO-A has not been achieved. Identifying the molecular pathways that regulate the activity of MAO-A in the brain is crucial for developing new drug targets for precise control of MAO-A activity. Over the last few decades, several regulatory pathways of MAO-A consisting of Kruppel like factor 11 (KLF11), Sirtuin1, Ring finger protein in neural stem cells (RINES), and Cell division cycle associated 7-like protein (R1) have been identified, and the influence of social stress on these regulatory factors evaluated. This review explores various aspects of these pathways to expand our understanding of the roles of the HPA axis and MAO-A regulatory pathways during social stress. The first part of this review introduces some components of the HPA axis, explains how stress affects them and how they interact with the 5-HT system in the brain. The second part summarizes the novel regulatory pathways of MAO-A, which have high potential as novel therapeutic targets for depression.